Bibliographic Analysis of the Digital Divide and Literacy in New Technologies - De Benito-Castanedo, Jesús (2017)
This article analyzes the digital divide in Spain from a bibliographic perspective, focusing on the digital literacy as a fundamental, pedagogical element. Educational interventions in new technologies have been the subject of analysis, both at an academic and institutional level. Many ideas and strategies have emerged from this analysis to carry out digital literacy projects. Thus, the present paper reflects the conceptualization and current situation of the digital divide, considering the interventions in digital literacy as an essential element in the process of digital inclusion. The article culminates with simple guidelines to implement this type of educational actions; these guidelines also intend to be a useful tool for the educators’ work in the field of literacy in new technologies.